Selected Poems : Odes and Fragments - Sophocles (Book collections on Project MUSE., 2008)
Sophocles' tragedies--from Antigone to Oedipus Tyrannus--are filled with highly wrought, vivid, and emotionally powerful poetry. Yet most translations sacrifice the poetry to convey only the sense of the lines as dramatic speech. This is the first book in English to present Sophocles exclusively as a poet, and the only volume to reveal the full force and beauty of his verse. With a fresh and consistent attention to structure, language, and rhythm across Sophocles' writings, Reginald Gibbons has translated a selection of odes from Sophocles' surviving plays as well as fragments from his lost works. What emerges is a genuinely new sense of a Sophocles who was as much poet as dramatist. Bringing the Greek poet and his world surprisingly close to us, these translations also restore a sense of the long continuity of poetry. Complete with an introduction, this edition reveals Sophocles' poetic brilliance as never before.